A vaccine against serogroup B Neisseria meningitidis: Dealing with uncertainty - Andrews, S; Pollard, A (Lancet, 2014)
Neisseria meningitidis is an important cause of invasive bacterial infection in children worldwide. Although serogroup C meningococcal disease has all but disappeared in the past decade as a direct result of immunisation programmes in Europe, Canada, and Australia, meningitis and septicaemia caused by serogroup B meningococci remain uncontrolled. A vaccine (4CMenB) has now been licensed for use in the European Union, comprising three immunogenic antigens (identified with use of reverse vaccinology) combined with bacterial outer-membrane vesicles. The vaccine has the potential to reduce mortality and morbidity associated with serogroup B meningococci infections, but uncertainty remains about the breadth of protection the vaccine might induce against the diverse serogroup B meningococci strains that cause disease. We discuss drawbacks in the techniques used to estimate coverage and potential efficacy of the vaccine, and their effects on estimates of cost-effectiveness, both with and without herd immunity. For parents, and clinicians treating individual patients, the predicted benefits of vaccination outweigh existing uncertainties if any cases can be prevented, but future use of the vaccine must be followed by rigorous post-implementation surveillance to reassess its value to health systems with directly recorded epidemiological data. © 2014 Elsevier Ltd.